Um estudo sobre o trabalho educativo com famílias no programa mais educação sob as perspectivas ecológica e da educação social - Thiecker, Gabriele Daiana (2014)
Full Time Schooling in Brazil has been developed by federal programs. The program intitled “Mais Educação” is one of the examples of these initiatives which operates in “counter shift” of public school teaching. The guidelines of the Program evidence that among other pedagogical elements, this one intends to involve the community and the care takers responsible for the students, and therefore, it suggests the need to identify and understand how the educational work with families operates. This study is inserted in the line of Management, Education and Public Policy Research, the Postgraduate Education Program Unilasalle and the objective to investigate the educators´ practices with families in the perspective of bioecology of human development and the principles of Social Education in the context of the Program “Mais Educação” and its routines. The research has as theoretical and methodological basis the principles of Urie Bronfenbrenner and Social Pedagogy. The data were collected in two municipal schools of two cities from the metropolitan city of Porto Alegre-RS. The methodology of the study was qualitative with the following strategies: systematic field observation and semi-structured interviews with educators. The results have as basis the observations made and the analysis of teachers’ perception. It was evident the distance of the student´s responsibles at the routine of the activities of the Program Mais Educação. Such fact highlights that the guidelines of the Program are not followed and can have effects in the development of the students. Social Education serves as a basis to the social and educational practices of teachers at the strategy of Full Time Education in Brazil and establishes links and a sociallook towards the participants of these programs of compensatory education.